Research on Economic Evaluation Methods and Project Investment Strategies for Gas Power Generation Based on the Natural Gas Industry Chain and Gas–Electricity Price Linkage in China - Hua Wei; Feng Li; Zixin Hong; Haifeng Jiang (Fuels)
In recent years, due to the spike in natural gas spot prices, gas-fired power corporations’ operating costs have skyrocketed. Traditional power generation corporations have gradually been withdrawing from gas power generation investment, replaced by oil and gas enterprises with upstream resources. The development of gas-fired power plants helps to maintain the stability of the power grid and has a positive effect on the realization of carbon neutrality goals. At present, most of the financial evaluation methods for gas power generation projects tend to focus on the static tariffs of the project itself and lack consideration for the overall contribution to the industry chain and the latest “gas–electricity price linkage” mechanisms in China, leading to oil and gas enterprises reducing investment in gas-fired power plants due to yield constraints. In this paper, a financial evaluation methodology for gas power generation projects based on the industrial chain and the “gas–electricity price linkage” mechanism was proposed. The investment return characteristics of specific gas power generation projects under the “gas–electricity price linkage” mechanism in different provinces were revealed through this methodology. Considering the characteristics and industrial development trends in major provinces in China, investment and operation strategies for gas power generation were proposed. These studies provide oil and gas enterprises with references and suggestions for future investment decisions for new gas power generation projects.